Looking In, Looking Out: Jews and Non-Jews in Mutual Contemplation : Essays for Martin Goodman on His 70th Birthday - Czajkowski, Kimberley; Friedman, David A. (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2024., 2024)
Martin Goodman's forty years of scholarship in Roman history and ancient Judaism demonstrates how each discipline illuminates the other: Jewish history makes best sense in a broader Greco-Roman context; Roman history has much to learn from Jewish sources and evidence. In this volume, Martin's colleagues and students follow his example by examining Jews and non-Jews in mutual contemplation. Part 1 explores Jews' views of inter-communal stasis, the causes of the Bar Kochba revolt, tales of Herodian intrigue, and the meaning of "Israel." Part 2 investigates Jews depiction of outsiders: Moabites, Greeks, Arabs, and Roman authorities. Part 3 explores early Christians' (Luke, Jerome, Rufinus, Syriac poetry, Pionius, ordinary individuals) views of Jews and use of Jewish sources, and Josephus's relevance for girls in 19th century Britain.